Handbook of industrial refractories technology principles, types, properties and applications - Carniglia, Stephen C. (Noyes Publications, 1992)
This book covers the range of industrial refractory materials and forms: properties and their measurement, applications, manufacturing, installation and maintenance techniques, quality assurance and statistical process control. Contents: Foundations of Hot Processing; Foundations of Refractory Application; Principles of Thermal Stability; Principles of Corrosion Resistance; The Working Refractory Product Line; The Insulating Refractory Product Line; Refractory Practice Design Properties; Refractory Manufacture; Refractory Installation and Maintenance.
Keywords: Refractory materials -- Handbooks, manuals, etc.; elektronické knihy; electronic books